1996
DOI: 10.1021/bi960178r
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of an NH2-Terminal Fragment of T4 DNA Polymerase and Its Complexes with Single-Stranded DNA and with Divalent Metal Ions

Abstract: We report the crystal structure of an NH2-terminal 388-residue fragment of T4 DNA polymerase (protein N388) refined at 2.2 A resolution. This fragment contains both the 3'-5' exonuclease active site and part of the autologous mRNA binding site (J. D. Karam, personal communication). The structure of a complex between the apoprotein N388 and a substrate, p(dT)3, has been refined at 2.5 A resolution to a crystallographic R-factor of 18.7%. Two divalent metal ion cofactors, Zn(II) and Mn(II), have been located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
99
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 28 publications
12
99
0
1
Order By: Relevance
“…A ϩ T-rich sequences are expected to facilitate local melting (16,17); yet, the G255S-DNA polymerase, unlike the wild type enzyme, could not take advantage of A ϩ T richness to separate the primer strand from the template strand. These results are most consistent with a recent crystallographic study of the exonuclease domain showing the location of Gly-255 in a critical loop structure (14) and support a proofreading mechanism in which amino acid residues in the exonuclease domain of the T4 DNA polymerase assist the strand separation process.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…A ϩ T-rich sequences are expected to facilitate local melting (16,17); yet, the G255S-DNA polymerase, unlike the wild type enzyme, could not take advantage of A ϩ T richness to separate the primer strand from the template strand. These results are most consistent with a recent crystallographic study of the exonuclease domain showing the location of Gly-255 in a critical loop structure (14) and support a proofreading mechanism in which amino acid residues in the exonuclease domain of the T4 DNA polymerase assist the strand separation process.…”
supporting
confidence: 90%
“…Residue Gly-255 and the surrounding region has been identified as a "hot spot" by our genetic selection methods for mutations that decrease proofreading (9). Although it has only been assumed that Gly-255 resides in the exonuclease domain based on protein sequence comparisons to KF (2-5), recent structural studies of an amino-terminal fragment of the T4 DNA polymerase verify that residue Gly-255 is located in the exonuclease domain (14).…”
mentioning
confidence: 99%
“…Structural and mutagenesis studies of DNA pol I suggest a role for this conserved Tyr at the active site (31,32). For T4 DNA pol mutations at this Tyr affect both the polymerase and the exonuclease activities (35,39). An alternative Exo III motif, named Exo III⑀, has been proposed based on mutagenesis studies of the exonuclease domain of Bacillus subtilis DNA pol III (40).…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies of DNA pol I indicate that the Tyr in the YXXXD sequence of the Exo III motif interacts with a phosphate oxygen of the 3Ј-terminal nucleotide in the DNA substrate (31). In contrast, the equivalent Tyr in the Exo III motif of bacteriophage T4 DNA pol points away from the active site (35). Currently, structural data of exonucleases containing the HXAXXD sequence in the Exo III motif are not available to access the roles of the amino acids within this sequence.…”
Section: Table I Expression Of Trex Proteins In E Colimentioning
confidence: 99%
“…Structural studies of a T4 DNA polymerase fragment showed that the glycine residue at position 255 resides at the tip of a ␤ hairpin loop within the exonuclease domain of the protein (11), but so far there is no structure of full-length T4 DNA polymerase in complex with DNA. The homologous polymerase from bacteriophage RB69, gp43, which shares 61% sequence identity with the T4 polymerase (12), has been crystallized in an apoform (13) and with both normal and damaged DNA (14 -17).…”
mentioning
confidence: 99%